An ecohydraulics virtual watershed: Integrating physical and biological variables to quantify aquatic habitat quality. Issue 2 (21st December 2018) - Benjankar, Rohan; Tonina, Daniele; McKean, James A.; Sohrabi, Mohammad M.; Chen, Qiuwen; Vidergar, Dmitri
Abstract: Advances in remote sensing coupled with numerical modelling allow us to build a "virtual ecohydraulics watershed" at the micro‐habitat scale. This approach is an integrated modelling framework with a cascade of models including physical (hydrologic, hydraulic, and stream water temperature) and biological (fish habitat) modelling at a resolution and extent important for aquatic and terrestrial organisms. We applied this approach to quantify the impacts of discharges and water temperature on habitat quality and spatial/temporal habitat use patterns of bull trout, a federally listed species along the South Fork Boise River. We coupled process‐based snow melt and hydrologic models to predict water availability within the watershed. The model fed one‐ and two‐dimensional hydrodynamic models to predict stream hydraulics and water temperature using high‐resolution (meter scale) river bathymetric data. This information was then used in an aquatic habitat modelling to characterize habitat quality distribution as a function of discharges. Our results showed that the summer thermal regime of river system would alter available habitat. The high spatial resolution analysis allows modelling to predict the importance of lateral habitats, which serve as vital refugia during high‐flow events for many fish species. The advances in remote sensing, numerical modelling, and understanding of physical‐biological processes provide us an opportunity to conceptualize new process‐based integrated modelling tools to analyse human impacts at a catchment scale, for example, dam operation and climatic variability on aquatic habitat and status, and further to develop restoration protocols in a virtual domain before field studies are developed and/or structures built.